A Virtual Clinic for DDH Pavlik Harness Monitoring. Issue 2 (25th November 2021) - Merchant, Rajiv M.; Khan, Shehzaad A.; Douglas, Christine; Edel, Penina; Khan, Tahir; Eastwood, Deborah M.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Pavlik harness (PH) treatment is successful in treating over 90% of newborns with developmental dysplasia of the hip (DDH). There is a need for close supervision, frequent adjustments, size changes, and monitoring of complications. This paper aims to provide a safe criterion for remote follow-up of DDH patients treated in a PH to reduce the risk of COVID-19 (coronavirus disease 2019) exposure to patients, parents, and health practitioners. Methods: All infants with stable hips (Graf I, IIa/b/c/d, treated III/IV) with consenting parents after appropriate counseling were enrolled in a virtual clinic. Clinics were conducted using the NHS "Attend anywhere" virtual link service by an extended scope practitioner-specialist physiotherapist and a clinical nurse specialist. The virtual clinic group was compared with a matched cohort of patients from 2018/2019. Results: A total of 141 patients were referred to the neonatal hip clinic; 45 patients were eligible for harness treatment and 20 patients were selected for virtual clinics. In total, there were 35 virtual clinic appointments. Each of the patients had an average of 1.7 virtual appointments ranging from 1 to 3 (26.3% of total number of clinics). Age at presentation of the treated group was 7±4.2 weeks and control group 5.7±5.5 weeks ( P =0.59). PH duration of the study group was 9±2.6 weeks and the control group, 7.8±2.5 weeks ( P =0.12). There were no missed complications at the follow-up face-to-face appointment. Patients saved an average of 76 km total travel distance. Conclusions: This study demonstrates adequate evidence that children requiring routine follow-up appointments involving PH adjustment, skincare, and identification of clinical anomalies, can be treated and followed up safely using virtual clinics. Clinical triage of suitable patients for virtual clinic provision must always be made by experienced clinicians. Children presenting with Graf IIa, IIb, IIc, IId, as well as those with stable and improving Graf III at initial diagnoses, had successful treatment with virtual clinic follow-up appointments in this study. Level of Evidence: Level IV.